Risk Factors for Post-Endoscopic Retrograde Cholangiopancreatography Pancreatitis in the Indomethacin Era - A Prospective Study - Perdigoto, David N. (2019)
Background and Aims: Although endoscopic retrograde cholangiopancreatography (ERCP) is an essential procedure used to treat conditions affecting the biliopancreatic system, it can lead to several complications. Post-ERCP pancreatitis (PEP) is the most frequent one, with an incidence ranging from 3 to 14%. Our aim was to assess the potential risk factors associated with PEP occurrence in patients undergoing ERCP with indomethacin prophylaxis. Methods: Prospective, single-center, real-world observational study (January to December 2015) with inclusion of patients submitted to ERCP, where relevant patient-related and procedure-related data had been collected. Patients had to have been admitted for a minimum of 24 h in order to establish the presence of early complications. All patients were submitted to PEP prophylaxis with 1 or 2 methods: rectal indomethacin and pancreatic duct (PD) stenting. Results: A total of 188 patients who had undergone ERCP were included (52.7% women; mean age 69.2 ± 16.0 years) and PEP was diagnosed in 13 (6.9%). PEP prophylaxis consisted of indomethacin in all cases (100%) and PD stenting in 7.4%. The pancreatitis was mild in 11 patients (84.6%) and severe in the other 2. One of them died (0.5%). None of the patient-related risk factors were associated with changes in PEP probability. Of all patients, 33.0% had 2 or more procedure-related risk factors. A higher number of synchronous procedure-related risk factors showed a statistically significant correlation with PEP occurrence, p = 0.040. Conclusions: The 6.9% PEP rate is considered acceptable since 33.0% patients had a medium-high risk for PEP due to challenging biliary cannulation. The total number of procedure-related risk factors seems to play a critical role in the development of PEP despite indomethacin prophylaxis.